Little Red and the very hungry lion - Smith, Alex T. (Scholastic Press, an imprint of Scholastic Inc., 2016)
In this version of Little Red Riding Hood, set on the African plains, Little Red realizes what the Very Hungry Lion is up to, and teaches him a lesson before generously sharing her donuts with him.